HUBUNGAN INDEKS MASSA TUBUH DENGAN DENSITAS MINERAL TULANG PADA PEREMPUAN DEWASA MUDA (ASSOCIATION BETWEEN BODY MASS INDEX AND BONE MINERAL DENSITY IN YOUNG ADULT FEMALE ) - Budi Setyawati; Sri Prihatini; Wasilah Rochmah; Retno Pangastuti (Persagi, 2011)
ABSTRACT Background: Body Mass Index (BMI) is a good indicator for measurement of Bone Mineral Density (BMD), so it is often used to predict BMD. Objective: To assess the association between BMI and status of BMD among 242 young adult female who were 25-35 years of age and who underwent quantitative ultrasound bone densitometry (QUS) scan. Method: We used data from the study on “Determinants of Risk Factors for Osteoporosis at three provinces in Indonesia” that was undertaken by the Center for Research and Development in Nutrition and Food, 2007. Design of the study was cross-sectional study. The dependent variable was BMD; the independent variable was BMI; and the confounding variables were: acceptors of hormonal contraception, physical exercises, calcium intake, ratio of Ca: P intake, consumptions of supplements, sources of phytoestrogen, fruits and vegetables. Result: Ca intake < 500 mg/day had a risk twice to low BMD than adequate Ca intake, the association was statistically significant (p<0.05). There are no association between BMI and BMD (p>0,05). Other variables as hormonal contraception, physical exercise, protein intake, Ca: P ratio intake, consumption of supplements source of phytoestrogen, fruits and vegetables have no association with BMD. Conclusion: There are no significant association between BMI and BMD. Calcium intake was the only risk factor for low BMD. Keywords: osteoporosis, body mass index, bone mass density, bone density, young adult woman ABSTRAK Latar Belakang: Indeks massa tubuh (IMT) adalah indikator yang baik untuk pengukuran densitas mineral tulang (DMT). Tujuan: Mengkaji hubungan antara IMT dan status DMT pada perempuan dewasa muda usia 25-35 tahun. Metode: Data yang digunakan berasal dari penelitian ’Faktor Determinan Risiko Osteoporosis di Tiga Provinsi di Indonesia’ yang dilakukan Pusat Penelitain dan Pengembangan Gizi dan Makanan pada 2007. Penelitian ini merupakan studi observasional-analitis dengan rancangan cross-sectional. Variabel terikat: DMT, variabel bebas: IMT, variabel perancu: peserta KB hormonal, kebiasaan berolahraga, asupan kalsium (Ca), rasio asupan Ca:P, konsumsi suplemen, konsumsi sumber fitoestrogen dan buah-sayuran. Hasil: Asupan Ca < 500 mg/hari berisiko dua kali mengalami DMT rendah dibandingkan asupan Ca yang cukup, hubungan ini bermakna secara statistik (p<0,05). Tidak ditemui hubungan antara IMT dan DMT (p>0,05). Variabel lain seperti rasio asupan Ca:P, kebiasaan konsumsi suplemen, sumber fitoestrogen, buah-sayuran, kebiasaan berolahraga dan peserta KB hormonal tidak memiliki hubungan dengan DMT. Kesimpulan: Tidak terdapat hubungan yang signifikan antara IMT dan DMT. Asupan kalsium merupakan faktor risiko terjadinya DMT rendah. [Penel Gizi Makan 2011, 34(2): 93-103] Kata kunci: osteoporosis, indeks massa tubuh, densitas mineral tulang, densitas tulang, wanita dewasa muda.